(untitled) (World Science, 2018)
Objective: make a comparative analysis of the voice of the index (VHI) and endoscopic studies in the pathology of the voice of children. Material and Methods: The study involved 87 children, from 6 months to 14 years. The clinical study included fibrorinolaryngoscopy with video fixation (C-MAC, K. Storz, Ø-2,7 mm) and a survey of parents (or guardians) of children at the Uzbek version of the voice handicap index (pVHI), with sub- sections (functional - F, the physical - P and emotional - E). Results: endoscopic diagnosed laryngitis 20,6% (n = 18), functional 16,1% (n = 14) and mutational 9,2% (n = 8), dysphonia, benign larynx (respiratory papillamatosis) - 18.4 % (n = 16), the vocal cords paresis - 5.7% (n = 5), the vocal folds nodules 26.4% (n = 23), throat structure anomalies (acquired) 3,4% (n = 3). The survey revealed pVHI average points total pVHI and its sub-group of patients were as follows: F - 13,94, P - 15.48, E - 12.15 and T - 41.58, which is significantly higher than the group of healthy children and children with functional disorders of voice. Conclusions: Fibrolaryngoscopy with the smallest diameter of the lumen of the laryngoscope with video fixation allowed to quickly ascertain the diagnosis of organic disease of the larynx in children. In addition, the survey pVHI allowed to differentiate the severity of the vocal apparatus, to conduct timely special endoscopic diagnosis of vocal cord diseases.